2021
DOI: 10.1002/eco.2347
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining forest disturbance thresholds for managing cumulative hydrological impacts

Abstract: Forest disturbance thresholds, defined as those at or above which significant hydrological impacts are caused, are important guides to support forest and watershed management decisions for protecting hydrological functions and minimizing negative environmental impacts. Our literature review suggests that despite their significance, the research on this topic is surprisingly limited (<20 publications), where the paired watershed experiments (PWEs) primarily designed for detecting hydrological responses to fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Classical experiments of management interventions in paired catchments showed that the minimum area required for a change from high to low-biomass vegetation (or vice versa) to cause change in the annual flow is the widely accepted threshold of 20% of the watershed (Bosch & Hewlett 1982;Brown et al 2005). However, a recent study in Canada (Wei et al 2021) found a range from 12 to 25% of the watershed, instead of a sharp threshold. Differences within the range can be due to the intervention itself (type, intensity, and duration), characteristics of the watershed (size, landscape, slope, soil, geology etc.…”
Section: Increasing Tree Canopy Cover and Biomass Reduces The Effecti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Classical experiments of management interventions in paired catchments showed that the minimum area required for a change from high to low-biomass vegetation (or vice versa) to cause change in the annual flow is the widely accepted threshold of 20% of the watershed (Bosch & Hewlett 1982;Brown et al 2005). However, a recent study in Canada (Wei et al 2021) found a range from 12 to 25% of the watershed, instead of a sharp threshold. Differences within the range can be due to the intervention itself (type, intensity, and duration), characteristics of the watershed (size, landscape, slope, soil, geology etc.…”
Section: Increasing Tree Canopy Cover and Biomass Reduces The Effecti...mentioning
confidence: 99%
“…Differences within the range can be due to the intervention itself (type, intensity, and duration), characteristics of the watershed (size, landscape, slope, soil, geology etc. ), and climate (Zhang et al 2017; Wei et al 2021). This threshold has a crucial implication for restoration planning when water yield is among the expected outcomes of the intervention within a watershed.…”
Section: There Is a Threshold Of Forest Cover Change Within A Watersh...mentioning
confidence: 99%
“…Several studies show that differences in physiological processes (transpiration) and physical processes (evaporation) before and after the change in forest species composition account for most of the variability in streamflow that cannot be attributed to climate (Wei et al, 2021;Yu et al, 2019). Due to differences in xylem anatomy type, the transpiration rates of birch trees are higher than that of larch trees for a given stem diameter (Caldwell et al, 2016;Ford et al, 2011).…”
Section: Impacts Of Forest Changes On Annual Streamflowmentioning
confidence: 99%
“…When the changes in forest accumulate to a substantial level, streamflow can be altered significantly which would cause problems for the PWE approach (Wei et al, 2021). Therefore, the history of forest change must be precisely quantified in both control and treatment watersheds; otherwise, the application of the PWE approach is questionable for long-term studies.…”
Section: Paired Watershed Experiments Approachmentioning
confidence: 99%